Abuse of Law in the Context of the European Tax Law: Analyse of the Question of Direct Taxation of Cross Border Self-Employers Incomes - Tahiraj, Rezarta (Richtmann Publishing, 2012)
The notion of the abuse of law it is a concept that reveals in private law in many jurisdictions. In relation to the European TaxLaw, the principle of the abuse of law it is consistent with the principles of primacy and effectiveness. Recently, the Court of Justice ofthe European Union has resorted to the concept quite often when dealing with the reach of the fundamental freedoms guaranteed by theTreaty of the European Union. The proposed paper applies the abuse of law concept to European Tax Law related to the question of thedirect taxation of cross border self-employers incomes. Of central importance here are the rules issued from the Court of Justice of theEuropean Union that legitimize, when assessing the absence of the harmonized rules in the field of the direct taxation, restrictivemeasures of the fundamental freedoms of establishment and to provide services in relation of the self-employers. The proposed paperstarts by exploring the context of the debate related to the abuse of law with respect to European Tax Law. The general elements of theabuse of law concept are then presented. It is an interpretative concept that looks at the dominant purpose of a particular legal provision.The proposed paper explores this concept with respect to potential abuses in relation of direct taxation of cross border self-employersconcerning the freedoms of establishment and to provide services. The proposed paper concludes with the conclusion that theadaptation of the restrictive measure of the freedoms of establishment and to provide services in relation of the direct taxation of crossborder self-employers are justified only in the general interest and for which need the proportionality principle.